Characterizing dilatation energy of released gas from underground coal seam by drilling boreholes - Yu, B.; Cheng, Jianwei; Yang, S.; Wang, D. (2014)
© 2014, Springer Science+Business Media Dordrecht. In order to precisely measure the dilatation energy of the released gas from underground coal seam, this paper initiated a study on the dilatation energy of gas released from underground coal seam by drilling boreholes. Firstly, an in-depth analysis is made on the two major factors causing outburst, which are crustal stress and gas. By establishing mathematical models of unit coal potential energy and gas dilatation energy, authors make a detailed calculation and results comparison. It verifies that the gas dilatation energy is the important and main energy source of a coal seam outburst. Then, the characteristics of dilatation energy of coal seam gas are further stated. Secondly, based on the analysis on the types and features of gas discharge from coal seam and according to the flow field type, this paper divided gas dilatation energy into unidirectional gas dilatation energy, radial gas dilatation energy, and spherical gas dilatation energy. Then, with the assistant of establishing the mathematical model, the software of MATLAB® is used to make numerical calculation on gas dilatation energy release. The results show that dilatation energy of gas released from underground in-seam by drilling boreholes could reflect that coal gas’s ability of expansion work under normal occurrence conditions. Finally, according to the theory of coal seam gas dilatation energy and the features of gas flowing in reducing pipe, on-site measuring method and testing equipment are worked out to measure underground gas dilatation energy. The results of field measurements in a coal mine show that the gas dilatation energy could completely reflect the physical and mechanical properties of crustal stress, gas, and coal. It could be used as a most effective indicator in judging whether coal and gas outburst might occur. Thus, it presents good scientific and practical significances for predicting coal seam outburst.